2020
DOI: 10.3390/genes11020236
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous In Situ Conservation of Faba Bean Landraces in Tunisia: A Case Study

Abstract: Cultivation of faba bean (Vicia faba L.) in Tunisia is largely based on improved varieties of the crop. However, a few farmers continue to produce local cultivars or landraces. The National Gene Bank of Tunisia (NGBT) recently launched a collection project for faba bean landraces, with special focus on the regions of the North West, traditionally devoted to cultivating grain legumes, and where around 80% of the total national faba bean cultivation area is located. The seed phenotypic features of the collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This evidence confirms the genetic correspondence among the commercial material and the reference varieties, including the Italian varieties widely spread in Tunisia. These results will be very useful to start the plant material certification process in Tunisia, following the procedures commonly adopted [38]. On the contrary, the germplasm recovered from Azmour and Ras Jbal clustered separately, indicating a differentiation from the National germplasm, and underlying the presence of an original genetic component never investigated before.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This evidence confirms the genetic correspondence among the commercial material and the reference varieties, including the Italian varieties widely spread in Tunisia. These results will be very useful to start the plant material certification process in Tunisia, following the procedures commonly adopted [38]. On the contrary, the germplasm recovered from Azmour and Ras Jbal clustered separately, indicating a differentiation from the National germplasm, and underlying the presence of an original genetic component never investigated before.…”
Section: Discussionmentioning
confidence: 78%
“…Today, there is a strong interest in the recovery and preservation of agro-biodiversity, and several projects are in place to avoid the loss of this patrimony, setting up recovery collections [32][33][34][35]. In Tunisia, although there are institutions, such as the Olive Institute, that hold a large number of olive genotypes, it is still necessary to enlarge the existing collection and develop new conservation management strategies [36][37][38]. At the same time, it is crucial to improve the plant material certification circuit to be more competitive in the global market, offering plant material with high quality standards [39].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [7] explained that domestication, the oldest breeding method recognized by human history, has reduced genetic diversity by changing the pattern of gene expression. Another breeding method that has been associated with reduced crop genetic diversity is intraspecific Diversity 2020, 12, 303 2 of 14 hybridization, through the utilization of similar parents [8]. For example, Fu et al [3] explained that the reduction in the average genetic diversity among Canadian oat genotypes that have been released since 1950 may due to the utilization of the same resistant parental lines, which was supported by the finding of allelic reduction, as revealed by simple sequence repeat (SSR) markers.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these markers combination resulted as being effective to cluster the sweet potato clones in agreement with their geographical origin [ 14 ]. The last report included in this Special Issue focused on molecular markers supporting the in situ conservation of faba bean ( Vicia faba L.) landraces in Tunisia [ 15 ]. The seed phenotypic features of the collected samples were analyzed, together with the genetic diversity and population structure, by using simple sequence repeat markers, highlighting the genetic stability of the population under study.…”
mentioning
confidence: 99%
“…The seed phenotypic features of the collected samples were analyzed, together with the genetic diversity and population structure, by using simple sequence repeat markers, highlighting the genetic stability of the population under study. These findings suggested that farmers applied international best practices for the in situ conservation of agricultural crops [ 15 ].…”
mentioning
confidence: 99%